PENINGKATAN PRODUKSI MELALUI PERBAIKAN PROSES DAN PENAMBAHAN VARIAN RASA MIE PADA KELOMPOK SEJALAN NAGARI SIMALANGGANG KABUPATEN LIMA PULUH KOTA - Harly, Resolinda; Febrianti, Firshty; Ediana, Dina; Amri, M; Indra, Ristapawa; Elmiati, Reni; Triani, Hera Dwi; Azizah, Nur; Syahla, Tiara (LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) Universitas Andalas, 2024)
The Sejalan Group is one of the Bundo Kanduang Small and Medium Industry groups in Jorong Koto Simalanggang Nagari, Payakumbuh District, Limapuluh Kota Regency. This group consists of 13 housewives who focus on food processing, including processing noodles made from fruit, vegetables and other food ingredients. The aim of this activity is community empowerment carried out in Nagari Simanggang through the transfer of knowledge, skills and technology to increase the production of Sejalan Group noodles. The stages of community service activities include preparation, implementation, evaluation and reporting stages. The problems faced by the Sejalan Group in producing noodles are the drying process and the taste of the noodles. Drying is done naturally by drying in the sun. This affects the quantity and quality of the noodle products produced. The results obtained from this activity were an increase in the group's noodle production in line with the presence of a drying tool in the form of an oven. Apart from that, adding flavors to noodles with the addition of chicken and shrimp flavors is able to increase consumer appeal for noodle products and increase the income of the Sejalan Group. The addition of chicken and shrimp is also aimed at increasing the nutritional content of noodle products. From this activity, it can be concluded that the community service activities that have been carried out have had a positive effect on increasing the business of the women of the Sejalan Group.